Tanggung Jawab Bank X Terhadap Pembayaran Qris Yang Tertunda: Perspektif Hukum Perdata - Karenina Maheswari Wihita (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The ease of transactions is increasingly finding a bright spot with the presence of QRIS as a payment system that is needed in achieving effective, fast, and easy words. The issuance of QRIS on August 17, 2019 which is digital-based is an innovation of Bank Indonesia which has full authority in managing the Indonesian payment system. The innovation provided is inseparable from the government's goal of encouraging the National Non-Cash Movement (GNNT) as a government program that aims to depend on the community in using cash as a transaction medium. This has proven successful with the increasing number of QRIS usage in the community with the help of the role of banks as financial service providers that provide QRIS as a bank product. However, like the creation of technology, the shortcomings created in QRIS do not escape the system constraints that result in the payment system being disrupted. The impact of the problematic system makes the QRIS transaction carried out by the payer successful, but does not enter the QRIS holder's account (merchant). Losses arise in civil law for the merchant so that it is often restless when the system experiences problems. Because of this, this research is conducted to answer the problems that occur by reviewing the point of view of the legal responsibility of the bank which is obliged to provide solutions to the unrest that occurs. The form of compensation is also accompanied by an examination of the policies contained in a number of related regulations or from a legal perspective. Thus, in answering all research conducted, it is necessary to use qualitative research methods or empirical research using the interview method so that the data obtained comes from bank representatives. Hopefully, the results of this research can be applied as a solution in answering similar problems and become a recommendation in detailing elements in policies, provisions, and regulations relating to QRIS and banks.